Revolusi E-Commerce: Transaksi Digital dan Dampaknya Pada Pertumbuhan Ekonomi di ASEAN-5 - Hayati, Cucu; Hanifah, Hanifah; Sadiqin, Amin (Politeknik Negeri Padang, 2024)
This study analyzes the impact of e-commerce and digital transformation on economic growth in five ASEAN countries (Indonesia, Malaysia, Singapore, Thailand, and the Philippines) during the 2011-2021 period, using panel data and the Common Effect Model (CEM) or pooled data panel approach. The results show that digital payment has a positive and significant impact on economic growth, indicating the importance of digital payment adoption in enhancing economic activity in the region. On the other hand, e-commerce transaction value has a significant negative effect, which can be explained by the imbalance in value-added distribution and the concentration of capital on certain e-commerce platforms that do not support other sectors evenly. World digital competitiveness has a positive impact on GDP, showing that countries with higher digital competitiveness tend to have better economic growth. Total population contributes positively but has a minor influence on GDP, while labor force shows a significant negative effect, reflecting challenges in matching workforce growth with the rapidly evolving digital market demands.